TOSCANO, M. (2024) Contra Babel. Ensayo sobre el valor de las lenguas. Sevilla: Athenaica - Rosales, José María (Daimon Revista Internacional de Filosofia, 2026)
Reseña de TOSCANO, M. (2024) Contra Babel. Ensayo sobre el valor de las lenguas. Sevilla: Athenaica